A cross-sectional survey of medical and other groups’ awareness, perceptions, and willingness to use e-cigarettes during the COVID-19 pandemic - Deng, Ruihang; Yang, Chuang; Yuan, Yifang; Liang, Lifang; Yang, Xin; Wang, Xinyu; Tian, Jiao; Zhang, Yuxin; Wu, Xuekai; Dai, Haiyun (Frontiers in Public Health, 2024)
Background: In China, people's perceptions towards electronic cigarettes during Corona Virus Disease 2019 (COVID-19) pandemic compared with pre-pandemic conditions have not been explored. Exploring the perceptions of medical workers regarding e-cigarettes is crucial, as they serve as a trusted source of information and providers of smoking cessation counseling for smokers. This cross-sectional study was designed to explore the awareness and perceptions of e-cigarettes among Chinese medical and other groups in the context of the COVID-19 pandemic.(18-40, OR = 4.797, 95CI% = 0.930-24.744, P = 0.061; > 40, OR = 9.794, 95CI% = 1.683-56.989, P = 0.011).This study highlights the need to provide stress management for ecigarette users during the COVID-19 pandemic. E-cigarettes advertisements were the main source of information for young individuals to learn about e-cigarettes, and hence measures should be taken to restrict exposure of young individuals to e-cigarettes.Medical groups are less likely to use e-cigarettes, but misperceptions are still prevalent and are not well placed to provide smoking cessation counselling. This calls for additional training for such medical personnel to improve their capacity to provide necessary counselling to smokers.This study found that individuals tend to hold negative attitudes toward the awareness, perceptions, and willingness to use e-cigarettes. Medical groups are less likely to use e-cigarettes, but misperceptions are still prevalent among them. This calls for additional training for such medical personnel to improve their capacity to provide necessary counselling to smokers. E-cigarettes advertisements were the main source of information for young individuals to learn about e-cigarettes, and hence measures should be taken to restrict exposure of young individuals to e-cigarettes.